2011
DOI: 10.1124/jpet.111.185405
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Enzymatic Interactions Determine the Relative Amounts of Prostaglandins E2 and D2

Abstract: Prostaglandins (PGs) are a family of cellular messengers exerting diverse homeostatic and pathophysiologic effects. Recently, several studies reported significant increases of PGI 2 and PGF 2␣ after the inhibition of microsomal PGE synthase-1 (mPGES-1) expression, which indicated that PGH 2 metabolism might be redistributed when the PGE 2 pathway is blocked. To address the determinants that govern the relative amounts of PGs, we developed an in vitro cell-free method, based on liquid chromatography-tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
(51 reference statements)
0
27
1
Order By: Relevance
“…Supernatant sample preparation was similar to what we previously described (Cao et al, 2008;Yu et al, 2011). Briefly, a 500-ml aliquot of supernatant was spiked together with d 4 -PGE 2 and d 4 -PGD 2 as surrogate standards.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supernatant sample preparation was similar to what we previously described (Cao et al, 2008;Yu et al, 2011). Briefly, a 500-ml aliquot of supernatant was spiked together with d 4 -PGE 2 and d 4 -PGD 2 as surrogate standards.…”
Section: Methodsmentioning
confidence: 99%
“…The HPLC system was interfaced to a Thermo-Finnigan (San Jose, CA) TSQuantum triple quadruple mass spectrometer that was operated using negative ion electrospray. Isomeric PGD 2 and PGE 2 were measured using a SRM transition of m/z 351 to m/z 271, and the SRM transition of m/z 355 to m/z 275 was selected for the internal standards d 4 -PGE 2 and d 4 -PGD 2 (Cao et al, 2010(Cao et al, , 2011Yu et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoperoxide PGH 2 is a very unstable molecule, and its halflife at 37°C is known to be 5 min (19). It has been reported that PGH 2 converts non-enzymatically to various prostaglandins, including HHT and MDA (20,21).…”
Section: Imidazole Stacks On the Bound Heme And Inhibits Heme Oxidatimentioning
confidence: 99%
“…A similar chromatogram was reported in other article. 24,31 We currently speculated that these peaks were derived from multi form TXB2 with the equilibrium state.…”
Section: Chromatographic Separationmentioning
confidence: 99%